The prevalence of teenage pregnancy and early motherhood and its associated factors among late adolescent (15-19) years girls in the Gambia: based on 2019/20 Gambian demographic and health survey data - Bewuketu Terefe (BMC, 2022)
Abstract Introduction Pregnancy and early motherhood among teenage girls is the current issue of public health burden in developing countries. Although the Gambia has one of the highest adolescent fertility rates in Africa, there is no data record about it in The Gambia. Therefore, this study aimed to assess the prevalence of pregnancy and early motherhood and its determinants among late adolescent girls in the Gambia. Methods It is a secondary data analysis using the 2019-20 Gambian demographic and health survey data. A total of 2,633 weighted 15-19 years old girls were included in the study. Using Stata 14 version, a pseudo logistic regression analysis method was employed to declare factors significantly associated with pregnancy and early motherhood among 15-19 years old late-adolescent girls in the Gambia. Variables with a p-value of < 0.2 were entered into multivariable regression analysis, and after controlling other confounding factors adjusted odds ratio of 95% CI was applied to identify associated variables. Results Pregnancy and early motherhood were found in 13.42% of late adolescent Gambian girls. Logistic regression analysis depicted that a unit increase in adolescent age was positively significantly associated with pregnancy and early motherhood (adjusted odds ratio [aOR] = 2.15; 95% confidence interval [CI] = 1.93,2.39), after period ended knowledge of ovulatory cycle (aOR = 1.99; 95% CI = 1.23,3.22), being from a family size of greater than ten (aOR = 1.25; 95 CI = 1.01,1.55) times more likely to become pregnant and early motherhood than their counterparts respectively. In contrast, rich in wealth (aOR = 0.35; 95% CI = 0.23,0.54), having primary education (aOR = 0.58; 95% CI = 0.43,0.79), secondary and above education (aOR = 0.12; 95% CI = 0.09,0.17). Conclusion Pregnancy and early motherhood remain significant public health challenges in the Gambia. Strengthening female education, empowerment, reproductive health life skill training and awareness, encouraging disadvantaged females, and designing timely policies and interventions are urgently needed.